2016
DOI: 10.1111/evo.12853
|View full text |Cite
|
Sign up to set email alerts
|

Life span and reproductive cost explain interspecific variation in the optimal onset of reproduction

Abstract: Fitness can be profoundly influenced by the age at first reproduction (AFR), but to date the AFR-fitness relationship only has been investigated intraspecifically. Here we investigated the relationship between AFR and average lifetime reproductive success (LRS) across 34 bird species. We assessed differences in the deviation of the Optimal AFR (i.e., the species-specific AFR associated with the highest LRS) from the age at sexual maturity, considering potential effects of life-history as well as social and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 73 publications
(164 reference statements)
3
48
0
Order By: Relevance
“…Our results strengthen the importance of taking into account age and sex when studying life histories, even among monogamous species in which both sexes exhibit similar parental care1291129. Based on a unique long-term monitoring of know-age marked individuals in a population of a territorial vulture, we found that sex asymmetries constrained the age of recruitment and the local survival of breeding individuals, but not breeding success.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our results strengthen the importance of taking into account age and sex when studying life histories, even among monogamous species in which both sexes exhibit similar parental care1291129. Based on a unique long-term monitoring of know-age marked individuals in a population of a territorial vulture, we found that sex asymmetries constrained the age of recruitment and the local survival of breeding individuals, but not breeding success.…”
Section: Discussionsupporting
confidence: 76%
“…Differences in age-dependent demographic parameters between sexes are also common in nature1011, especially among species showing intense competition for mates (polygynous species)1012, and/or body-sized dimorphic species with asymmetric parental roles13. However, sex-specific life-histories exist even in monogamous species with low sexual body-size dimorphism and similar parental investment in reproduction911.…”
mentioning
confidence: 99%
See 3 more Smart Citations